Examining How Junior High School Students Understand on Vibration and Wave Topics in HOTS Questions - Islamiyah, Kurnia; Koes-H, Supriyono; Taufiq, Ahmad; Yana, Annisa Ulfa (Kasuari: Physics Education Journal (KPEJ), 2024)
This study offers fresh perspectives on the difficulties students encounter when grasping concepts related to vibrations and waves. It highlights the need for creating more effective Higher Order Thinking Skills (HOTS) questions to enhance student comprehension.This research aims to examining the understanding of junior high school students about vibrations and waves regarding HOTS questions. The method used in this study is descriptive analysis in which 68 students of 9th grade junior high school participated and answered five multiple-choice HOTS questions about vibration and waves topic. The reliability of the questions used in this study was 0.845, indicating a high level of reliability. The results of the study showed that overall, 66% of students understand the concept of vibrations and wave, but 21% of students were categorized as very less at understanding HOTS questions related to vibration and waves well. In addition, students’ ability in understanding question with indicator C6 was also the lowest when compared to indicator C5 and C4. It was concluded that a wide deficit exists among them regarding the higher conceptual knowledge of physics. Such findings could be a starting point for making necessary adjustments in curriculum and teaching methodology at junior high school physics.